Development model for competency improvement and national vocational qualification support frames in Automotive technology - Muhammad Nurtanto; Herminarto Sofyan; Pardjono Pardjono; Suyitno Suyitno (International Journal of Evaluation and Research in Education (IJERE), 2020)
BNSP technical competence gets high legality on the side of the industry, while not all test participants can acquire it. Until now, studies that discuss relevant competency test models on automotive engine technology are still limited, not specific or even non-existent. The objective of this research is to produce a Competency Test Model for Engine Tune Up-System Injection and determine the characteristics after the model is applied. The subject of development consists of assesses (vocational education graduates, workers and educators), experts, and assessors from related Professional Certification Institutions (LSP). Instrument validation was conducted through expert judgment and feasibility trials. Reliability tests were performed using alpha and interrater coefficient analysis. The results of the test analysis include (1) competency test model assessment using the CBA approach; (2) competency dimension elements in instruments development are in the form of TS, TMS, CMS, EMS, and JRES; and (3) the characteristics of competency assessment include equipment verification of adequacy, avoiding impartiality, meeting requirements, transparent and accounTable, and able to produce recommendations as "competent" and "non-competent". The obtained findings showed that the developed competency test model could be used as a reference for use in vocational education.